Learning on the quick and cheap: gains from trade through imported expertise - James R. Markusen; Thomas F. Rutherford (Deutsche Bundesbank, 2005)
Gains from productivity and knowledge transmission arising from the presence of foreign firms has received a good deal of empirical attention, but micro-foundations for this mechanism are weak . Here we focus on production by foreign experts who may train domestic unskilled workers who work with them. Gains from training can in turn be decomposed into two types: (a) obtaining knowledge and skills at a lower cost than if they are self-taught at home, (b) producing domestic skilled workers earlier in time than if they the domestic economy had to rediscover the relevant knowledge through "reinventing the wheel". We develop a three-period model in which the economy initially has no skilled workers. Workers can withdraw from the labor force for two periods of self study and then produce as skilled workers in the third period. Alternatively, foreign experts can be hired in period 1 and domestic unskilled labor working with the experts become skilled in the second period. We analyze how production, training, and welfare depend on two important parameters: the cost of foreign experts and the learning (or "absorptive") capacity of the domestic economy.
Keywords: F13; F23; 330; learning; transmission mechanism; multinationals; imported; Wissenstransfer; Qualifikation; Aussenwirtschaft; Facharbeiter